2018
DOI: 10.1111/jon.12516
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Neuroimaging in the Determination of Brain Death

Abstract: BACKGROUND AND PURPOSEBrain death determination (BDD) is primarily a clinical diagnosis, where death is defined as the permanent loss of brainstem function. In scenarios where clinical examinations are inaccurate, ancillary imaging tests are required. The choice of ancillary imaging test is variable, but the common denominator for all of them is to establish a lack of cerebral blood flow. The purpose of this study was to compare the diagnostic accuracy and interrater reliability of different ancillary imaging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 24 publications
2
29
1
1
Order By: Relevance
“…Another recent study from Macdonald et al reported the diagnostic accuracy and inter-rater reliability of different ancillary imaging tests used for brain death in 74 patients. They showed that CTA along with CTP and radionuclide scan had a specificity and positive predictive value of 100% [10]. These results certainly add to the growing medical literature that supports the use of CTA as a reliable ancillary imaging test in confirming the brain death.…”
Section: Computed Tomography Angiography (Cta)mentioning
confidence: 78%
See 4 more Smart Citations
“…Another recent study from Macdonald et al reported the diagnostic accuracy and inter-rater reliability of different ancillary imaging tests used for brain death in 74 patients. They showed that CTA along with CTP and radionuclide scan had a specificity and positive predictive value of 100% [10]. These results certainly add to the growing medical literature that supports the use of CTA as a reliable ancillary imaging test in confirming the brain death.…”
Section: Computed Tomography Angiography (Cta)mentioning
confidence: 78%
“…For whole brain CTP, Ancillary Imaging Tests for Confirmation of Brain Death DOI: http://dx.doi.org /10.5772/intechopen.86516 they also showed a sensitivity of 100% to confirm the diagnosis of brain death [24]. MacDonald et al showed similar sensitivity [10].…”
Section: Computed Tomography Perfusion (Ctp)mentioning
confidence: 95%
See 3 more Smart Citations